The private patient - James, Phyllis Dorothy, 1920-2014 (Penguin, 2009)
The scar on Rhoda Gradwyn's face was to be the death of her... When the notorious investigative journalist, Rhoda Gradwyn, books into Mr Chandler-Powell's private clinic in Dorset for the removal of a disfiguring and long-standing scar, she has every prospect of a successful operation and the beginning of a new life. But the Manor holds a secret and deadly enemy. While she lies drowsily recovering from the anaesthetic a white-shrouded figure stealthily enters her bedroom and within minutes Rhoda is dead. Dalgliesh and his team, called in to investigate the murder, and later a second equally horrific death, find themselves confronted with problems even more complicated than the question of innocence or guilt.